Numerical study of the 1996 Chimbote slow earthquake and tsunami (7.6 Mw) - Jiménez, C. (2015)
On February 21, 1996, an earthquake shook the northern region of Peru. This event generated a tsunami with 2-3 m height waves. From the analysis and the signal processing of 15 broadband teleseismic stations, a waveform inversion was performed to obtain the focal mechanism and source time function indicating a complex rupture process. The total duration of the rupture was 75 s, a rather high value for a relatively small earthquake. The calculated scalar seismic moment was 3.8 × 1020 Nm, which corresponds to a moment magnitude of 7.6 Mw. The slip distribution is heterogeneous, consistent with the source time function, with a maximum slip of 6.6 m around the main asperity concentrated in an area of 30×30 km2. Coseismic deformation field was calculated for 28 sub-faults, which was used as the initial condition of the tsunami propagation. Synthetics mareograms were calculated for Chimbote and Salaverry with maximum heights of 1.8 m and 1.0 m, respectively.